STRATEGI KOMUNIKASI PT. AGUNG AUTOMALL PANGKALAN KERINCI DALAM MENANGANI KELUHAN PELANGGAN - Pardede, Fenny Akhira; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Competition in the field of the automotive industry is increasingly tight.Similar products ,price competition, customers are getting smarter in choosing, wants and needs of customers and customer expectations are getting higher.Complaints are feedback that are attributed from customers to the company. PT Agung Automall Kerinci handle customer complaints which is services section and sales section. Handling customer complaints is included in customer relationship activities. The way to handle certainly different in some places like city and village. This research aims to analyze the communication strategy undertaken PT. Agung Automall Kerinci in terms of analyzing constituent/customer, analyze the message, and analyzing the response.This study used qualitative methods, data collectted based on the reality on the ground through observation, interviews, and documentatiois research. Informants of this research took 8 persons which is 1 Customer Relations Coordinator, 1 Sales Supervisor, 2 Advisor service, 1 Pre Delivery Service, and 3 customers who ever submitted complaints using the purposive technique.The study result showed that the communication strategy of PT Agung Automall Kerinci in analyzing constituent is by analyzing how the characteristics of the customers. Ranging from education, jobs, residence environment , the type of their car,to personal privte life of the customers like their tribe nor their origin. As for analyzing the message and completion of the problems are not directly to the core of the problems. The approach was using persuasive approach by giving attention to getting empathy. Communication media in conveying the message by face to face While in analyze customer response is using Customer Satisfaction Level (CSL) survey.and then the company using Focus Group Discussion(FGD), after that they doing follow up. PT Agung Automall Kerinci in the response analyzes customers is with the level of customer satisfaction survey of procurement (CSL) and then going on the company doing the FGD, after that do a follow-up. From resesrcher observation on customer response, disovered that customers are satisfied with the results of performance and service provided by the company, however the customers are less satisfied with equipment which avaliable in PT. Agung Automall Pangkalan Kerinci.